Tubular markers in children with insulin-dependent diabetes mellitus - Çalışkan, Salim; Fıçıcıoglu, Can; Hacıbekiroğlu, Münire; Mıkla, Şerare; Kasapçopur, Özgür; Sever, Lale; Aydın, Ahmet; Arısoy, Nil (The Turkish Journal of Pediatrics, 1997)
The aim of the present study was to investigate the prevalence of tubular dysfunction and to assess the clinical significance of low-molecular-weight proteinuria and enzymuria in children with insulin-dependent diabetes mellitus (IDDM). N.acetyl-beta-D-glucosaminidase (NAG) and beta-microglobulin ( β_2 M) excretion was determined in 52 children with insulin-dependent diabetes mellitus and 28 controls. Patients were grouped according to the duration of diabetes: group 1 (n = 7): less than one year; group 2 (n = 27): one to five years; groups 3 (n = 18): greater than five years. Both parameters were significantly increased in groups 2 and 3 compared to controls. Urinary β_2 M levels correlated significantly with albuminuria and HbA 1c , while urinary NAG levels correlated only with HbA 1c .Two to four samples were obtained from 35 of 52 diabetic patients in the study group at one-month intervals. Of these, 23 patients had elevated NAG levels, and 22 patients increased β_2 M excretion. However, only six patients displayed persistent enzymuria, and nine low-molecular-weight proteinuria. The mean (SD) of coefficients of variation of each patient was 50.45 (± 28.24) for NAG and 68.25 (± 42.57) for β_2 M excretion.We concluded that early tubular dysfunction and/or damage occurs in IDDM but is not established in the majority of children.
Keywords: beta2-microglobulin; insulin-dependent diabetes mellitus; n-acetyl-beta-D-glucosaminidase